Influence of modification and cooling speed on the process of eutectic crystallization of cast iron - L. Z. Pisarenko (Литьë и металлургия)
The executed investigations are aimed at finding ways to produce high-quality cast iron, especially at electrocasting, when the melt's crystallization tendency upon metastable system is particularly high.